CCNP Switch portable command guide - Empson, Scott; Roth, Hans (Indianapolis, IN : Cisco Press, 2010)
This guide summarizes all CCNP certification-level Cisco IOS Software commands, keywords, command arguments, and associated prompts, providing you with tips and examples of how to apply the commands to real-world scenarios.
rua 9/9/13
Loans
Keywords: Packet switching (Data transmission); Computer networks; Telecommunications engineers